The influence of human capital and the mediating effect of innovation practices toward Malay restaurant performance / Mohd Syaifuddin Mohd Alias - Mohd Alias, Mohd Syaifuddin (2022)
The main objective of this study is to investigate the structural relationships between human capital (HC), innovation practices (IP), and restaurant performance (RP) in Malay restaurants. The aim is to identify the influence of human capital on how innovation practices would be used for restaurant growth, profitability, and sustainability. Besides that, this study examined how the mediating effect of innovation practices after receiving the influence of human capital eventually affects restaurant performance. This research utilized purposive or judgemental sampling. The data was collected through questionnaires answered by 507 respondents from the top management of sampled Malay restaurants (owners, managers, and assistant managers). After a thorough analysis, this study eventually revealed that human capital, innovation practices, and restaurant performance are valid constructs. Furthermore, findings also revealed that there are relationships between human capital and restaurant performance, innovation practices, and performance, as well as human capital and innovation practices. Additionally, this study found that innovation practices mediated human capital and restaurant performance. The relationship between human capital, innovation practices, and restaurant performance was validated through Structural Equation Modelling (SEM). Based on the confirmed analysis, restaurant performance can be achieved through the decision of human capital to apply innovation practices in Malay restaurants. These findings are essential to the Malay restaurants especially in Malaysia to assess the benefit of using innovation practices as well as the experience and education in human capital. This study also discussed the limitations and future research.